Budżetowa metoda zarządzania przedsiębiorstwem produkcyjnym - Koszela, Dariusz (Budget Method of a Production Enterprise Management, 2006)
Aiming at the increase of effectiveness of economic organizations management caused that decentralization of these systems of organization management became more common. Management decentralization consists of both passing over entitlements to the lower levels of management and the increase in independence of lower level organizational units. One of the form of enterprise decentralization, and at the same time one of the basic instruments of management accounting, is marking off its responsibility centers. Budget process should be introduced evolutionary. The starting point is working out of raport about the state of a center, which in connection with previously executed analysis of good and bad sides of the company will allow to adapt the budget forms to the individual activity of individual centers. While creating budgets we use traditional method for both production centers, centers of administration and support of enterprise management i.e. branches such as accountancy, financial, economic, legislative, and administrative. The control of budget execution is carried out on two levels. The first is control within the responsibility center, and the second control is executed by the controller. The results are analyzed, taking into consideration the planned budget premises and the results reached in the given period.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 175-182